The extraterritorial application of selected human rights treaties - Costa, Karen da (Graduate institute of international and development studies, 2013)
"In recent years, the question of whether and to what extent states are bound by human rights treaty obligations when they act abroad has given rise to considerable debate in academic circles, courtrooms and military operations. Focusing on treaties considerably jeopardized during the 'war on terror', namely the International Covenant on Civil and Political Rights, the European Convention on Human Rights and the Convention against Torture, The Extraterritorial Application of Selected Human Rights Treaties takes stock of the key developments informing the discussion to date. Together with the wording of treaties, critical analysis is made of the ensuing interpretation of treaty provisions by monitoring bodies and states parties. A way forward in this debate is suggested, accommodating conflicting interests while preserving the effective protection of basic rights"--Back cover.